Mulheres, tempo e trabalho: direitos de conciliação entre a vida social e laboral no ordenamento jurídico brasileiro - Rafael, Letícia Felix [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This study aims to investigate the existence of Time Conciliation Rights in the Brazilian legal system - more specifically those that stipulate boundaries between work, social and family life, in an attempt to harmonize them. This is justified due to the asymmetry between family responsibilities, which are directly related to the sexual division of labour in both the public and private spheres. Therefore, the hypothetical-deductive approach and the quantitative analysis of data provided by renowned institutes, such as the IBGE, are used as a method of approach, in order to understand the sociological and political aspects of the issue, taking as a starting point the intersectional feminist theory. Regarding the method of procedure, the choice was for the historical and legal-dogmatic, with the purpose of finding the origins of the structural problems that interfere in the female protagonism within the labor market, as well as the existing international regulations on the subject and the incorporation or not to domestic law. Therefore, it appears that Brazil does not recognize the Conciliation Rights, although there is provision for some measures such as maternity leave and paternity leave, however, depending on who is in charge of the government, the rights of women is negatively affected, thus accentuating social and economic inequalities, mainly due to the impacts of the COVID-19 crisis. Despite the challenging scenario, there are pockets of resistance promoting advances, incorporating themes such as parental leave and recognition of unpaid childcare work for retirement purposes in the public debate.

O presente estudo se propõe a investigar a existência dos Direitos de Conciliação de Tempos no ordenamento jurídico brasileiro - mais especificamente aqueles que estipulam fronteiras entre a vida laboral, social e familiar, em busca de harmonizá-los. Isso se justifica em virtude da assimetria entre as responsabilidades familiares, as quais estão diretamente relacionadas com a divisão sexual do trabalho tanto no âmbito público quanto no privado. Para tanto, utiliza-se como método de abordagem o hipotético-dedutivo e a análise quantitativa de dados fornecidos por institutos de renome, a exemplo do IBGE, a fim de compreender os aspectos sociológicos e políticos da questão, tomando como ponto de partida a teoria feminista interseccional. No tocante ao método de procedimento, a escolha foi pelo histórico e dogmático-jurídico, com o propósito de encontrar as origens dos problemas estruturais que interferem no protagonismo feminino dentro do mercado de trabalho, bem como as normativas internacionais existentes sobre o tema e a incorporação ou não ao direito interno. Diante disso, verifica-se que o Brasil não reconhece os Direitos de Conciliação, apesar de haver previsão de algumas medidas como a licença-maternidade e licença-paternidade, no entanto, a depender de quem está à frente do governo, o direito das mulheres trabalhadoras é afetado de forma negativa, acentuando, assim, as desigualdades sociais e econômicas, principalmente pelos impactos da crise de COVID-19. Apesar do cenário desafiador, há focos de resistência promovendo avanços, incorporando temas como licença parental e reconhecimento do trabalho não remunerado de cuidados com filhos para fins de aposentadoria no debate público.
Women, time and labor: conciliation rights between the social and working life in the Brazilian legal system
Keywords: Labor law; Women; Gender relations; Sexual division of labour; Direito do trabalho; Mulheres; Relações de gênero; Divisão sexual do trabalho